Copper paste, method for producing copper paste, and method for forming metal film

By using copper paste without copper particles, copper hydride particles and dispersion medium to sinter in the air in a short time at low temperature, the problem of copper paste being unable to sinter in the air and silver paste being high in the prior art is solved, and the cost of copper paste being achieved is achieved. The metal film with excellent conductivity is formed, and the cost of solar cells is reduced.

CN119296844APending Publication Date: 2025-01-10CHANGZHOU JUHE NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310815730.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing copper paste cannot be sintered in the air, and the precious metal properties of using silver paste lead to high cost of solar cells, and the sintering conductivity of copper hydride nanoparticles coated with long chain organic compounds is insufficient.

Method used

A copper paste containing no copper particles is used, consisting of only copper hydride particles and a dispersion medium, and copper hydride particles are produced by wet reduction method, and sintered in an atmosphere containing oxygen at low temperature and in a short time.

Benefits of technology

Sintering in the air at low temperatures and in a short time is achieved, forming a metal film with excellent conductivity, reducing the production cost of solar cells, and avoiding the increase in sintering temperature and time caused by long-chain organic compounds coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004321627820000171
    Figure BDA0004321627820000171
  • Figure BDA0004321627820000181
    Figure BDA0004321627820000181
Patent Text Reader

Abstract

Provided are: a copper paste which can be sintered in an air atmosphere under low-temperature and short-time conditions; a method for producing the copper paste; and a method for forming a metal film. This copper paste contains copper hydride particles and a dispersion medium, and does not contain copper particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copper paste, a method for producing the copper paste, and a method for forming a metal film. Background Art

[0002] In the HJT cell structure which is one of the structures of a crystalline solar cell, a method of forming electrodes at 200° C. or less using a silver paste having a thermosetting resin such as an epoxy resin as a binding material is widely known.

[0003] However, the conductive component is silver, which is a precious metal, so as the popularity of solar cells increases, there is a concern that the supply will be limited. In addition, silver itself is expensive, which leads to an increase in the price of solar cells themselves. In order to further popularize solar cells, it is required to use materials other than silver.

[0004] As an alternative, a copper paste using copper particles has been studied, but it is difficult for copper particles to be sintered in air to form an electrode.

[0005] In order to solve the above problems, a method of coating the copper surface with silver has been proposed. However, since the coating with silver increases the number of steps, it is difficult to achieve low prices.

[0006] Patent Document 1 proposes copper hydride nanoparticles in which the surface of copper particles is coated with a long-chain organic compound. However, since the surface is coated with the long-chain organic compound, sintering is difficult and the conductivity of the metal film after sintering is insufficient.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent document 1: International Patent Publication No. 2004 / 110925 Summary of the invention

[0010] Problems to be solved by the invention

[0011] In order to solve the above-mentioned disadvantages in Patent Document 1, a method for producing copper hydride nanoparticles without using a long-chain organic compound and a composition of a metal paste using the method are proposed. The composition of the metal paste has a metal filler containing a mixture of copper hydride nanoparticles and copper particles as an essential element. However, the above-mentioned metal paste cannot be sintered in air and can only be sintered in a nitrogen atmosphere.

[0012] The present invention has been made in view of the above problems, and the technical problem to be solved is to provide a copper paste that can be sintered in an atmosphere containing oxygen at low temperature and in a short time, a method for producing the copper paste, and a method for forming a metal film.

[0013] Technical solutions to technical problems

[0014] The present invention has been studied in depth in view of the above technical problems, and as a result, it has been found that a copper paste can be sintered in an atmosphere containing oxygen at low temperature and in a short time, and the copper paste contains copper hydride particles and a dispersion medium but does not contain copper particles, thereby completing the present invention.

[0015] That is, the above-mentioned problems of the present invention can be solved by the following means.

[0016] 1. A copper paste comprising copper hydride particles and a dispersion medium, but not containing copper particles.

[0017] 2. The copper paste according to item 1 above, which does not contain a conductive filler other than the copper hydride particles.

[0018] 3. The copper paste according to item 1 above, wherein only the copper hydride particles are used as a conductive phase.

[0019] 4. The copper paste according to item 1 above, wherein the dispersion medium is a liquid dispersion medium.

[0020] 5. The copper paste according to item 4 above, wherein the dispersion medium is a liquid dispersion medium having a hydroxyl group.

[0021] 6. The copper paste according to item 5 above, wherein the liquid dispersion medium having a hydroxyl group is water, an alcohol dispersion medium, or an ether dispersion medium.

[0022] 7. The copper paste according to any one of items 4 to 6, wherein the liquid dispersion medium is only water.

[0023] 8. The copper paste according to item 1 above, wherein the surface of the copper hydride particles is coated with formic acid.

[0024] 9. The copper paste according to item 1 above, wherein the content of the dispersion medium is 0.05 to 1 part by weight relative to 1 part by weight of the copper hydride particles.

[0025] 10. The copper paste according to item 1 above, wherein the surface of the copper hydride particles is not coated with a long-chain organic compound.

[0026] 11. The copper paste according to item 1 above, further comprising a resin binder.

[0027] 12. The copper paste according to item 11 above, wherein a content of the resin binder is 0.0001 parts by weight or more and less than 0.05 parts by weight relative to 1 part by weight of the copper hydride particles.

[0028] 13. A method for producing a copper paste, the method comprising:

[0029] a step of dispersing copper hydride particles in a dispersion medium,

[0030] This method does not add copper particles.

[0031] 14. The method for producing a copper paste according to item 13 above, wherein no conductive filler other than the copper hydride particles is added.

[0032] 15. The method for producing a copper paste according to item 13 above, wherein the conductive phase of the copper paste is only the copper hydride particles.

[0033] 16. The method for producing a copper paste according to item 13 above, wherein the dispersion medium is a liquid dispersion medium.

[0034] 17. The method for producing a copper paste according to item 16 above, wherein the dispersion medium is a liquid dispersion medium having a hydroxyl group.

[0035] 18. The method for producing a copper paste according to item 17 above, wherein the liquid dispersion medium having a hydroxyl group is water, an alcohol dispersion medium or an ether dispersion medium.

[0036] 19. The method for producing a copper paste according to any one of items 16 to 18, wherein the liquid dispersion medium is only water.

[0037] 20. The method for producing a copper paste according to item 13 above, wherein the surface of the copper hydride particles is coated with formic acid.

[0038] 21. The method for producing a copper paste according to item 13 above, wherein the dispersion medium is used in an amount of 0.05 to 1 part by weight based on 1 part by weight of the copper hydride particles.

[0039] 22. The method for producing a copper paste according to item 13 above, wherein in the step of dispersing the copper hydride particles in the dispersion medium, the copper hydride particles are dispersed in a mixture of the dispersion medium and a resin binder.

[0040] 23. The method for producing a copper paste according to item 22, wherein an amount of the resin binder added is 0.0001 parts by weight or more and less than 0.05 parts by weight relative to 1 part by weight of the copper hydride particles.

[0041] 24. A method for forming a metal film, the method comprising: a step of sintering the copper paste according to any one of items 1 to 12 above in an atmosphere containing oxygen.

[0042] 25. The method for forming a metal film according to item 24 above, wherein the sintering temperature is 200° C. or less and the sintering time is 1 minute to 10 minutes.

[0043] 26. The method for forming a metal film according to item 24 above, wherein the atmosphere containing oxygen is an air atmosphere.

[0044] Effects of the Invention

[0045] According to the present invention, it is possible to provide a copper paste that can be sintered in an atmosphere containing oxygen at a low temperature and in a short time, a method for producing the copper paste, and a method for forming a metal film. DETAILED DESCRIPTION

[0046] 1. Copper paste

[0047] The present invention relates to a copper paste for forming an electrode of a solar cell. The copper paste contains copper hydride particles and a dispersion medium, but does not contain copper particles.

[0048] The copper paste having the above configuration can provide a solar cell electrode having significantly superior conductivity even when fired in an atmosphere containing oxygen (eg, air atmosphere) compared to conventional copper pastes containing copper particles (simple copper particles).

[0049] The copper paste of the present invention contains copper hydride particles and a dispersion medium, but does not contain copper particles.

[0050] The copper hydride particles are copper particles containing hydrogen elements, exist in a state where copper atoms and hydrogen atoms are bonded, and can be decomposed into metallic copper and hydrogen when heated (for example, heated at a sintering temperature).

[0051] The above copper hydride particles can be manufactured by a wet reduction method. As a wet reduction method, it can include: a process of preparing a copper ion aqueous solution using a copper compound soluble in water; a process of adding an acid to the above aqueous solution to adjust the pH; a process of adding a reducing agent to the above aqueous solution to reduce the copper ions and generate copper hydride particles. It should be noted that in these processes, there is no process of adding or using the above long-chain organic compound.

[0052] In the copper ion aqueous solution preparation process, a water-soluble copper compound is dissolved in water. The water is not particularly limited, and distilled water and deionized water are preferably used from the viewpoint of having less adverse effects on the reaction of copper ions. The "water-soluble copper compound" is preferably a water-soluble copper salt, and specifically preferably copper sulfate, copper nitrate, copper formate, copper acetate, copper chloride, copper bromide, copper iodide, etc., and more preferably copper acetate and copper nitrate with high solubility in water. The concentration of the water-soluble copper compound in the aqueous solution is not particularly limited, and can be selected as needed. The water-soluble copper compound is 0.1 to 30 parts by mass, preferably 1 to 30 parts by mass, and more preferably 5 to 20 parts by mass relative to 100 parts by weight of the aqueous solution as a whole. When the water-soluble copper compound is too low, the productivity of the copper hydride particles is insufficient, and when the concentration of the water-soluble copper compound is too high, the yield of the copper hydride particles becomes poor.

[0053] In the above-mentioned pH adjustment process, an acid is added to lower the pH of the aqueous solution. As the above-mentioned acid, formic acid is preferably used. By adding formic acid, the pH of the aqueous solution is lowered to 3 or less, preferably to 2 to 3. By adjusting the pH of the aqueous solution to 3 or less, the copper ions in the aqueous solution are easily reduced by the reducing agent, and copper hydride particles are easily generated. If the pH of the aqueous solution exceeds 3, there is a risk of generating metallic copper particles instead of copper hydride particles.

[0054] In the above-mentioned step of generating copper hydride particles, the above-mentioned aqueous solution is adjusted to a pH of 3 or less, and then a reducing agent is added. As copper ions are reduced, copper hydride particles grow to obtain a suspension of copper hydride particles. In addition, the particle size of the hydride particles can be controlled by controlling the amount of the reducing agent, the reaction time, etc.

[0055] As the above-mentioned reducing agent, any reducing agent can be used as long as it can reduce copper ions. From the viewpoint of the good reduction effect of copper ions, preferably a metal hydrogen compound or hypophosphorous acid. As the above-mentioned metal hydride, lithium aluminum hydride, lithium borohydride, sodium borohydride, lithium hydride, potassium hydride, calcium hydride, etc. can be mentioned, preferably lithium aluminum hydride, lithium borohydride, sodium borohydride.

[0056] The amount of the reducing agent added can be selected according to the amount of copper ions, specifically, preferably 1.5 to 10 times the equivalent relative to the total amount of copper ions. If the amount of the reducing agent added is 1.5 times the equivalent relative to the copper ions or more, the reduction effect becomes sufficient. If the amount of the reducing agent added is 10 times the equivalent or less relative to the copper ions, the amount of impurities (sodium, boron, phosphorus, etc.) contained in the copper hydride particles can be suppressed.

[0057] The temperature of the aqueous solution when adding the reducing agent is preferably 5 to 60° C., more preferably 20 to 50° C. When the temperature of the aqueous solution is 60° C. or lower, decomposition of the copper hydride particles is suppressed, and when it is 5° C. or higher, there is no reduction in yield due to a reduction in reaction rate.

[0058] The average particle size of the copper hydride particles is 10 to 100 nm. When the average particle size is 100 nm or less, the melting temperature is sufficiently low, sintering is easy, and a dense conductive film with excellent conductivity is easily formed. On the other hand, when the average particle size is 10 nm or more, the chemical stability of the particles is increased. The average particle size of the copper hydride particles is preferably 10 to 80 nm, preferably 20 to 80 nm, and preferably 20 to 50 nm.

[0059] Preferably, formic acid is bonded to the surface of the copper hydride particles. The formic acid comes from the formic acid added in the pH adjustment step. By bonding formic acid to the surface of the copper hydride particles, at least a portion of the surface of the copper hydride particles is coated with formic acid, and oxygen in an atmosphere containing oxygen such as air can be inhibited from contacting the surface of the copper hydride particles. As a result, the chemical stability of the copper hydride particles can be further improved.

[0060] Whether formic acid is bonded to the surface of the copper hydride particle can be confirmed by measuring the IR spectrum of the copper hydride particle and confirming that there is no 1700 cm-1 band due to the expansion and contraction of C═O from formic acid that does not interact with the surface of the copper hydride particle. -1 There is absorption near or the absorption is small, and there is 1500 to 1600 cm caused by COO- from formic acid interacting with the surface of the copper hydride particles. -1 's absorption and implementation.

[0061] In addition to the above steps, a step of purifying the copper hydride particles may be included as necessary.

[0062] In the purification step, if the copper hydride particle suspension obtained in the step of generating copper hydride particles is left to stand, the copper hydride particles will aggregate and precipitate. The copper hydride particles can be purified by a method of redispersing the precipitate in a dispersion medium and then aggregating and precipitating the copper hydride particles again, thereby obtaining highly purified copper hydride particles.

[0063] As the dispersion medium used for purification, a mixed dispersion medium of water and methanol is preferred. When only water is used, the surface tension of water is large, so water cannot enter the pores of the agglomerates of copper hydride particles, and the purification effect is small. On the other hand, when only methanol is used, the dielectric constant of methanol is small, so impurities such as sodium cannot be freed as ions in the dispersion medium, and the purification effect is small.

[0064] The copper paste of the present invention is characterized in that it does not contain copper particles. The copper particles are metal single substance copper particles. By not containing copper particles, the copper paste can be sintered in an atmosphere containing oxygen at a low temperature and in a short time.

[0065] In the copper paste of the prior art, the copper particles are essential conductive fillers and are the main conductive fillers, accounting for at least 50% by mass of the total amount of the conductive fillers. The copper particles are different from the copper hydride particles of the present invention, do not contain hydrogen, and the manufacturing method is also different from the copper hydride particles of the present invention. In the copper paste of the prior art, if the copper particles as the essential conductive filler (and the main conductive filler) are missing, the copper paste cannot be formed.

[0066] However, a copper paste containing such copper particles cannot be sintered in an atmosphere containing oxygen such as an air atmosphere, and can only be sintered in a harsh atmosphere containing no oxygen such as a nitrogen atmosphere.

[0067] In order to solve this problem, the prior art proposes to combine copper hydride particles with reducing properties with the above copper particles to prepare a copper paste. In such a copper paste, the copper particles are still a necessary and main conductive filler, and the copper hydride particles are added as a reducing agent for the copper particles. However, such a copper paste still cannot be sintered in an atmosphere containing oxygen, and can only be sintered in a strict atmosphere that does not contain oxygen, such as nitrogen.

[0068] Therefore, in the present invention, a technical solution in which copper particles are not contained in a copper paste was discovered. Surprisingly, it was discovered that according to this technical solution, a copper paste can be obtained that does not need to be sintered in an atmosphere containing oxygen such as nitrogen but can be sintered at a low temperature and in a short time in an atmosphere containing oxygen such as air, and that can form a metal film with excellent conductivity.

[0069] Furthermore, surprisingly, when the copper paste of the present invention is sintered in a nitrogen atmosphere suitable for the copper paste of the prior art, a metal film having a conductivity that is even better than that of the copper paste of the prior art can be obtained.

[0070] In addition, in the copper paste of the present invention, the copper hydride particles are used as the main conductive filler. From the viewpoint of further effectively achieving the effect of the present application, it is preferred that the copper paste of the present invention does not contain a conductive filler other than the copper hydride particles. When the copper paste of the present invention does not contain a conductive filler other than the copper hydride particles, it will not adversely affect the behavior of the copper hydride particles during sintering, and a further excellent effect can be achieved. More preferably, in the copper paste of the present invention, only the copper hydride particles are used as the conductive phase. In this way, the copper hydride particles can form a metal film with excellent conductivity by sintering in an atmosphere containing oxygen at a very low temperature and in a short time during sintering.

[0071] In addition, another important feature of the present invention is that the surface of the copper hydride particles of the present invention is not coated with the long-chain organic compound. The surface of the copper hydride particles of the present invention is not bonded with a long-chain organic compound. The surface or interior of the copper hydride particles of the present invention do not contain a long-chain organic compound. The inventors of the present invention have found that when the surface of the copper hydride particles is coated with a long-chain organic compound, the sintering property of the copper paste containing such copper hydride particles deteriorates. Specifically, when the copper paste containing the copper hydride particles whose surface is coated with a long-chain organic compound is sintered, the sintering temperature becomes higher and the sintering time becomes longer due to the presence of the long-chain organic compound. Such a copper paste needs to have a sintering temperature of more than 400°C and a sintering time of more than 1 hour. If such a copper paste is sintered at a sintering temperature of less than 200°C, a conductive film with excellent conductivity cannot be obtained. In addition, due to the presence of the long-chain organic compound, carbon from the long-chain organic compound may remain in the conductive film obtained by sintering. Due to the residual carbon, the resistance of the conductive film becomes higher. Especially when sintering at low temperature and in a short time, the possibility of carbon residue becomes higher, and the amount of carbon residue is larger, which is very unfavorable for suppressing the resistance of the conductive film. The inventors of the present invention have proved through experiments that if the copper hydride particles in the technical solution of the present invention (such as the copper hydride particles in Example 1 of the present application) are replaced with copper hydride particles whose surface is coated with long-chain organic compounds and made into copper paste, such copper paste is sintered in air at 200°C (such as 120°C). It is impossible to obtain a resistance value similar to that of the embodiment of the present application. Therefore, the copper paste containing copper hydride particles whose surface is coated with long-chain organic compounds is not within the scope of the present invention, and the technical effect of the present invention cannot be achieved.

[0072] The above-mentioned long-chain organic compound refers to an organic compound having a carbon chain with more than 4 carbon atoms. The carbon chain may be a branched chain or a branched chain. Specifically, the following compounds are included. As long-chain organic compounds with more than 4 carbon atoms containing an amino group or an amide group, octylamine, decylamine, dodecylamine, tetradecylamine, hexadecylamine, octadecylamine, oleylamine, benzylamine, octadecylamide, and oleylamide can be cited. As long-chain organic compounds with more than 4 carbon atoms containing a sulfinyl group or a thioether-type sulfinyl group, decyl mercaptan, dodecyl mercaptan, trimethyl benzyl mercaptan, butyl benzyl mercaptan, hexyl sulfide, etc. can be cited. Examples of the long-chain organic compound having 4 or more carbon atoms and containing a hydroxyl group, a carboxyl group, a carbonyl group, or an ether-type oxygen group include dodecanediol, hexadecanediol, dodecanoic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, ethylene glycol monodecyl ether, diethylene glycol monodecyl ether, triethylene glycol monodecyl ether, tetraethylene glycol monodecyl ether, ethylene glycol monododecyl ether, diethylene glycol monododecyl ether, triethylene glycol monododecyl ether, tetraethylene glycol monododecyl ether, ethylene glycol monotetradecyl ether, and diethylene glycol monotetradecyl ether.

[0073] Furthermore, the copper paste of the present invention contains a dispersion medium.

[0074] The copper hydride particles manufactured by the above-mentioned copper hydride particle manufacturing method are filtered by ultrafiltration, most of the water is removed, and the particles are immediately dispersed in a dispersion medium to obtain a metal paste. From the viewpoint of good dispersibility and obtaining a metal film with further excellent conductivity, the dispersion medium is preferably a liquid dispersion medium. Compared to a dispersion medium with high viscosity, when a liquid dispersion medium is used, the copper hydride particles can be further uniformly dispersed, and using such a copper paste, a conductive film with uniform thickness can be formed. In addition, the above-mentioned liquid dispersion medium is preferably a liquid dispersion medium with a hydroxyl group. Different from copper particles, copper hydride particles (especially copper hydride particles coated with at least a portion of the surface by formic acid) have better compatibility with a liquid dispersion medium with a hydroxyl group. Even if a special dispersant is not added, or even if the copper hydride particles are not treated to improve dispersibility, the copper hydride particles can still be very uniformly dispersed in a liquid dispersion medium. Therefore, in the case of not containing copper particles, compared with a liquid dispersion medium without a hydroxyl group, a liquid dispersion medium with a hydroxyl group can be used to achieve a further uniform dispersion state, and a further uniform conductive film can be formed. Thereby, the conductivity of the metal film can be further increased.

[0075] Examples of the liquid dispersion medium having a hydroxyl group include water, alcohol dispersion medium, and ether dispersion medium.

[0076] Examples of the alcohol dispersion medium include methanol, ethanol, propanol, isopropanol, butanol, isobutanol, hexanol, and cyclohexanol.

[0077] Examples of the ether dispersion medium include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and butyl carbitol (BCA).

[0078] From the viewpoint of further improving dispersibility, a dispersion medium of water and ether is preferred, water or butyl carbitol (BCA) is more preferred, and water alone is more preferred. When water alone is used as a dispersion medium, a more dense and uniform conductive film can be formed when the copper paste is sintered, thereby forming a conductive film with further excellent conductivity.

[0079] The copper paste of the present invention does not contain copper particles. Moreover, the copper hydride particles have good compatibility with the dispersion medium, particularly the liquid dispersion medium having a hydroxyl group. Therefore, a copper paste in which the copper hydride particles are uniformly dispersed in the dispersion medium can be prepared simply by dispersing the copper hydride particles in the dispersion medium.

[0080] In the copper paste containing no copper particles of the present invention, the compatibility of the copper hydride particles with the dispersion medium, especially the liquid dispersion medium having a hydroxyl group, is good, and therefore, the amount of the dispersion medium can be reduced. In the copper paste of the present invention, the content of the dispersion medium is 0.05 to 1 part by weight, preferably 0.05 to 0.5 parts by weight, and more preferably 0.1 parts by weight, relative to 1 part by weight of the copper hydride particles. When the content of the dispersant is above the lower limit and above the upper limit, further excellent dispersibility can be achieved, and a metal film with excellent conductivity can be formed. In particular, when the content of the dispersant is above the lower limit, the copper hydride particles can be uniformly dispersed in the dispersion medium, and when the content of the dispersant is below the upper limit, sintering can be performed well at low temperature and in a short time. In addition, in the present invention, it is not necessary to use a dispersant of 1 part by weight or more relative to 1 part by weight of the copper hydride particles. When 1 part by weight or more of the dispersant is used relative to 1 part by weight of the copper hydride particles, the metal film of the present invention can be obtained, but the sintering time is prolonged, the sintering temperature is also increased, and the risk of failure during sintering is also increased.

[0081] The copper paste of the present invention may or may not contain a binder. In one embodiment, the copper paste preferably contains a binder. In one embodiment, the copper paste preferably does not contain a binder.

[0082] When the copper paste contains a binder, the adhesion between the obtained metal film and the substrate can be further improved, and a metal film with excellent reliability can be obtained.

[0083] When the copper paste does not contain a binder, sintering can be performed even at a lower temperature and in a shorter time. When the copper paste does not contain a binder, the behavior of the copper hydride particles during sintering will not be adversely affected, so a more dense and uniform metal film can be formed, and further excellent conductivity can be obtained.

[0084] As the above-mentioned adhesive, a resin adhesive is preferably used. As the above-mentioned resin adhesive, there is no particular limitation on the resin adhesive, and known resin adhesives (thermosetting resins, thermoplastic resins, etc.) used for metal pastes can be used, and preferably a resin component that is fully cured at the temperature during firing is selected.

[0085] Examples of the thermosetting resin include phenolic resins, epoxy resins, unsaturated polyesters, vinyl ester resins, diallyl phthalate, oligoester acrylate resins, xylene resins, bismaleimide triazine resins, furan resins, urea resins, polyurethane resins, melamine resins, silicone resins, acrylic resins, propylene oxide resins, Azine resin, etc., preferably phenolic resin, epoxy resin, Oxazine resin.

[0086] Examples of the thermoplastic resin include polyamide, polyimide, acrylic resin, ketone resin, polystyrene, and polyester.

[0087] From the viewpoint of achieving the effects of the present invention more effectively, acrylic resin is preferred.

[0088] In the present invention, copper particles are not contained, and the compatibility of the copper hydride particles and the resin binder is good. Therefore, a copper paste in which the copper hydride particles are uniformly dispersed in the resin binder can be formed with only a small amount of the resin binder.

[0089] In the copper paste of the present invention, the content of the resin binder is 0.0001 parts by weight or more and less than 0.05 parts by weight relative to 1 part by weight of the copper hydride particles. When the content of the resin binder is within the above range, a copper paste in which the copper hydride particles are uniformly dispersed in the resin binder can be formed, and a metal film with further excellent conductivity can be obtained. The content of the resin binder is preferably 0.0001 to 0.01 parts by weight, more preferably 0.0001 to 0.005 parts by weight, and even more preferably 0.0005 to 0.001 parts by weight relative to 1 part by weight of the copper hydride particles.

[0090] In addition, in the present invention, it is not necessary to use 0.05 parts by weight or more of the resin binder relative to 1 part by weight of the copper hydride particles. When 0.05 parts by weight or more of the dispersant relative to 1 part by weight of the copper hydride particles is used, the metal film of the present invention can be obtained, but there is a possibility that the coating property and handling property of the copper paste will be deteriorated, the sintering time will be prolonged, the sintering temperature will also be increased, and the risk of a defect occurring during sintering will also be increased.

[0091] 2. Method for manufacturing copper paste

[0092] The copper paste of the present invention can be produced by the following method. That is, the copper paste is produced by the process of dispersing the copper hydride particles of the present invention in the dispersion medium. In the dispersion process, no copper particles are added. In the dispersion process, no copper particles are used. The copper paste obtained by the process does not contain copper particles. In the copper paste obtained by the process, the conductive phase is only the copper hydride particles.

[0093] Specifically, most of water is removed from the copper hydride particle suspension obtained in the above-mentioned step of producing copper hydride particles by ultrafiltration, and the obtained copper hydride particles are immediately dispersed in a dispersion medium.

[0094] As described in “1. Copper paste”, the dispersant is preferably a liquid dispersion medium, more preferably a liquid dispersion medium having a hydroxyl group, further preferably water, alcohols or ethers, and most preferably water alone.

[0095] The dispersion medium is used in an amount of 0.05 to 1 part by weight relative to 1 part by weight of the copper hydride particles. Preferably, 0.05 to 0.5 parts by weight is used. More preferably, 0.1 parts by weight is used. By using the dispersion medium in such a range, a metal film having further excellent conductivity can be obtained.

[0096] In addition, it is preferred that at least a part of the surface of the copper hydride particles used in the method for producing the copper paste be coated with formic acid.

[0097] In addition to the above steps, a step of obtaining a copper paste by adjusting the amount of the dispersion medium so as to obtain a viscosity suitable for a pattern forming step such as screen printing may be performed as necessary.

[0098] In the case of a purification step, the following purification step is first performed: when the suspension containing the copper hydride particles is allowed to stand, the copper hydride particles are condensed and precipitated, the precipitate is redispersed in a dispersion medium, and the copper hydride particles are condensed and precipitated again to obtain highly purified copper hydride particles, and the above purification step is repeated multiple times, and the supernatant is removed to obtain clay-like copper hydride particles with a high solid content. The copper hydride particles are adjusted to a viscosity suitable for the pattern forming step using a dispersion medium suitable for the purpose of use.

[0099] In addition to the above steps, a step of mixing a known resin binder (thermosetting resin, thermoplastic resin, etc.) may be performed as necessary in order to obtain adhesion between the metal paste and the substrate.

[0100] When a resin binder is added, the copper hydride particles are dispersed in the mixture of the dispersion medium and the resin binder through the above-mentioned dispersing step, thereby further improving the dispersibility of the copper hydride particles in the dispersion medium and the resin binder.

[0101] When a resin binder is added, the amount of the resin binder added is 0.0001 to 0.1 parts by weight relative to 1 part by weight of the copper hydride particles.

[0102] 3.Method of forming metal film

[0103] In the present invention, the metal film is formed by sintering the copper paste of the present invention.

[0104] The copper paste of the present invention contains copper hydride particles and a dispersion medium but does not contain copper particles. Therefore, the copper paste can be sintered at a low temperature and in a short time even in an atmosphere containing oxygen.

[0105] In the present invention, in order to facilitate sintering, the atmosphere containing oxygen is preferably an air atmosphere. The air atmosphere does not need to be specially prepared, and air can be used directly.

[0106] In the present invention, the atmosphere containing oxygen may be other mixed gases containing oxygen, for example, a mixed gas of oxygen and nitrogen, a mixed gas of oxygen and an inert gas, a mixed gas of oxygen and air, etc.

[0107] In the present invention, sintering can be performed in an atmosphere not containing oxygen. The atmosphere not containing oxygen can be a nitrogen atmosphere or an inert gas atmosphere.

[0108] It should be noted that the copper paste of the present invention does not contain copper particles, so when sintered in an atmosphere containing oxygen, a metal film that has fully achieved the effect of the present invention can be formed. On the other hand, if sintered in an atmosphere containing only a single gas such as a nitrogen atmosphere, a further excellent effect can be achieved.

[0109] In the present invention, the sintering temperature may be 200° C. or lower. Since the copper paste of the present invention does not contain copper particles, it can be smoothly sintered even at such a low temperature of 200° C. or lower to obtain a metal film with excellent conductivity. The sintering temperature is preferably 180° C. or lower, preferably 160° C. or lower, preferably 140° C. or lower, and on the other hand, preferably 90° C. or higher, preferably 100° C. or higher, and preferably 110° C. or higher.

[0110] In addition, the copper paste of the present invention does not contain copper particles with large particle size, so the sintering time can be greatly shortened. The sintering time can be 1 minute to 20 minutes. It is preferably 1 minute to 10 minutes, more preferably 2 minutes to 10 minutes, more preferably 2 minutes to 5 minutes, and most preferably 3 minutes to 5 minutes. When the sintering time is within the above range, the copper hydride particles can be fully sintered, and a metal film with further excellent conductivity can be formed.

[0111] In addition, the sintering time can be appropriately adjusted according to the sintering temperature. When the sintering temperature is high, the sintering time can be appropriately shortened.

[0112] In the present invention, it is preferred that the sintering time is not too long. If the sintering time is too long, there is a possibility of adverse effects on the substrate and the adhesive.

[0113] Example

[0114] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the Examples.

[0115] Example 1

[0116] (Manufacturing of Copper Hydride Particles)

[0117] The copper hydride particles are produced by a method comprising the following steps: a step of preparing a copper ion aqueous solution using a copper compound soluble in water; a step of adding an acid to the aqueous solution to adjust the pH; a step of adding a reducing agent to the aqueous solution to reduce the copper ions to generate copper hydride particles, etc.

[0118] In a glass container, 5.2 g of copper acetate (II) hydrate was dissolved using 30 g of distilled water and 3.3 g of formic acid to prepare an aqueous solution containing copper ions. The pH of the aqueous solution was 2.6. While the aqueous solution was strongly stirred, 23 g of a 4% by mass sodium borohydride aqueous solution as a reducing agent was slowly added dropwise to the aqueous solution at 20°C. After the addition was completed, stirring was continued for 10 minutes to obtain a suspension of copper hydride particles.

[0119] The aggregates in the suspension were precipitated by centrifugal separation, and the precipitate was separated. The precipitate was redispersed in a mixed dispersion medium of 80 g of distilled water and 20 g of methanol, and then the aggregates were precipitated by centrifugal separation again, and the precipitate was separated. Purified copper hydride particles were obtained.

[0120] (Manufacturing of copper paste)

[0121] 1.0 g of the purified copper hydride particles were suspended in 0.1 g of water as a dispersion medium, and the mixture was stirred appropriately to obtain a copper paste. The copper paste did not contain any copper particles.

[0122] (Formation of Metal Film)

[0123] A groove with a width of 1 mm was formed on a 5 cm square Al2O3 substrate (Taizhou Jingwei Special Ceramics Co., Ltd., alumina ceramic sheet, 50×50×1 mm) by a 100 μm thick tape. The copper paste obtained in the above (manufacturing of copper paste) was applied to the above groove. The substrate coated with the copper paste was sintered at 120° C. in an air atmosphere for 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, and 10 minutes to form a metal film with a width of 1 mm and a length of 5 cm.

[0124] (Measurement of electrical conductivity of metal film)

[0125] The line resistivity of the metal film was measured when the sintering time reached 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, and 10 minutes.

[0126] Table 1 shows the components of the copper paste and the contents thereof, and Table 2 shows the evaluation results.

[0127] Example 2

[0128] In Example 1, purified copper hydride particles were obtained in the same manner as in Example 1 except that hypophosphorous acid was used as the reducing agent instead of sodium borohydride and the reaction was performed at 45°C.

[0129] A copper paste was prepared and a metal film was formed in the same manner as in Example 1, except that the copper hydride particles of Example 2 were used. The line resistivity of the metal film was measured.

[0130] Table 1 shows the components of the copper paste and the contents thereof, and Table 2 shows the evaluation results.

[0131] Example 3

[0132] In Example 1, purified copper hydride particles were obtained in the same manner as in Example 1 except that dimethylamine borane was used as the reducing agent instead of sodium borohydride and the reaction was performed at 45°C.

[0133] A copper paste was prepared and a metal film was formed in the same manner as in Example 1, except that the copper hydride particles of Example 3 were used. The line resistivity of the metal film was measured.

[0134] Table 1 shows the components of the copper paste and the contents thereof, and Table 2 shows the evaluation results.

[0135] Example 4

[0136] (Manufacturing of Copper Hydride Particles)

[0137] As in Example 1, 5.2 g of copper acetate (II) hydrate was dissolved in a glass container by 30 g of distilled water and 3.3 g of formic acid to prepare an aqueous solution containing copper ions. The pH of the aqueous solution was 2.6. While the aqueous solution was strongly stirred, 23 g of a 4% by mass sodium borohydride aqueous solution as a reducing agent was slowly added dropwise to the aqueous solution at 20° C. After the addition was completed, stirring was continued for 10 minutes to obtain a suspension of copper hydride particles.

[0138] The agglomerates in the suspension of the copper hydride particles are precipitated by centrifugation, and the precipitate is separated. After the precipitate is redispersed in a mixed dispersion medium of 80 g of distilled water and 20 g of methanol, the agglomerates are precipitated by centrifugation again, and after removing the supernatant, they are dispersed in methanol. For the dispersion, the agglomerates are precipitated by centrifugation, and the supernatant is removed again. The obtained agglomerates are redispersed in butyl carbitol (BCA) (Dow Chemical Company, trade name: Buthyl Carbitol), the agglomerates are precipitated by centrifugation, and after removing the supernatant, about 1 g of copper hydride particle agglomerates are obtained.

[0139] (Manufacturing of copper paste)

[0140] 0.1 g of butyl carbitol and 0.05 g of acrylic resin (10 wt % BCA solution) (Degussa; trade name: acrylic resin) were mixed with 1 g of the copper hydride particle agglomerates obtained as described above to obtain a copper paste.

[0141] (Formation of Metal Film)

[0142] A groove with a width of 1 mm was formed on a 5 cm square Al2O3 substrate (Taizhou Jingwei Special Ceramics Co., Ltd., alumina ceramic sheet, 50×50×1 mm) by a 100 μm thick tape. The above groove was coated with the copper paste obtained by (manufacturing of copper paste) in Example 4. The substrate coated with the copper paste was sintered at 120° C. in an air atmosphere for 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, and 10 minutes to form a metal film with a width of 1 mm and a length of 5 cm.

[0143] (Measurement of electrical conductivity of metal film)

[0144] The line resistivity of the metal film was measured when the sintering time reached 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, and 10 minutes.

[0145] Table 1 shows the components of the copper paste and the contents thereof, and Table 2 shows the evaluation results.

[0146] Example 5

[0147] (Manufacturing of Copper Hydride Particles)

[0148] In the same manner as in Example 1, purified copper hydride particles were obtained.

[0149] (Manufacturing of copper paste)

[0150] In the same manner as in Example 1, a copper paste was obtained.

[0151] (Formation of Metal Film)

[0152] A groove with a width of 1 mm was formed on a 5 cm square Al2O3 substrate (Taizhou Jingwei Special Ceramics Co., Ltd., alumina ceramic sheet, 50×50×1 mm) using a 100 μm thick tape. The copper paste of Example 5 was applied to the groove.

[0153] The sintering atmosphere was changed from the air atmosphere in Example 1 to a nitrogen atmosphere, that is, the substrate coated with the copper paste was sintered under the following conditions.

[0154] ① Sintering at 120°C in a nitrogen atmosphere for 1 minute, 2 minutes, 3 minutes, and 5 minutes to form a metal film.

[0155] ② Sintering at 200°C for 5 minutes in a nitrogen atmosphere to form a metal film.

[0156] (Measurement of electrical conductivity of metal film)

[0157] The line resistivity of the metal film was measured when the sintering time reached 1 minute, 2 minutes, 3 minutes, and 5 minutes at a sintering temperature of 120° C., and when the sintering time reached 5 minutes at a sintering temperature of 200° C.

[0158] Table 1 shows the components of the copper paste and the contents thereof, and Table 2 shows the evaluation results.

[0159] Example 6

[0160] (Manufacturing of Copper Hydride Particles)

[0161] By the same production method as in Example 1, purified copper hydride particles were obtained.

[0162] (Manufacturing of copper paste)

[0163] The water used as the dispersant in Example 1 was replaced with 0.1 g of butyl carbitol (BCA), that is, 1.0 g of the purified copper hydride particles were suspended in 0.1 g of butyl carbitol (BCA) as a dispersion medium and stirred appropriately to obtain a copper paste. The copper paste did not contain copper particles.

[0164] (Formation of Metal Film)

[0165] In the same manner as in Example 1, a metal film was formed.

[0166] (Measurement of electrical conductivity of metal film)

[0167] In the same manner as in Example 1, the line resistivity of the metal film was measured.

[0168] Table 1 shows the components of the copper paste and the contents thereof, and Table 2 shows the evaluation results.

[0169] Comparative Example 1

[0170] 1.0 g of the copper hydride particles obtained in the same manner as in Example 1 were suspended in 0.1 g of water as a dispersion medium, and 0.4 g of spherical copper powder (Mitsui Kinzoku Co., Ltd., 1100YM) having an average particle size of 1 μm was mixed therein to obtain a copper paste containing the copper hydride particles and the spherical copper powder.

[0171] The copper paste was sintered in the same manner as in Example 1 to form a metal film, and the line resistivity of the metal film was measured.

[0172] Table 1 shows the components of the copper paste and the contents thereof, and Table 2 shows the evaluation results.

[0173] Comparative Example 2

[0174] 1.0 g of the copper hydride particles obtained in the same manner as in Example 1 were suspended in 0.1 g of water as a dispersion medium, and 0.4 g of spherical copper powder (Mitsui Kinzoku Co., Ltd., 1100YM) having an average particle size of 1 μm was mixed therein to obtain a copper paste containing the copper hydride particles and the spherical copper powder.

[0175] The copper paste was sintered to form a metal film, and the line resistivity of the metal film was measured. The results are shown in Table 1.

[0176] The sintering atmosphere was changed from the air atmosphere in Example 1 to a nitrogen atmosphere, that is, the substrate coated with the copper paste was sintered under the following conditions.

[0177] ① In a nitrogen atmosphere, sintering was performed at 120°C for 1 minute, 2 minutes, 3 minutes, 4 minutes, and 5 minutes to form a metal film.

[0178] ② In a nitrogen atmosphere, sinter at 200°C for 5 minutes and 10 minutes to form a metal film.

[0179] (Measurement of electrical conductivity of metal film)

[0180] The line resistivity of the metal film was measured when the sintering time reached 1 minute, 2 minutes, 3 minutes, 4 minutes, and 5 minutes at a sintering temperature of 120°C, and when the sintering time reached 5 minutes and 10 minutes at a sintering temperature of 200°C.

[0181] Table 1 shows the components of the copper paste and the contents thereof, and Table 2 shows the evaluation results.

[0182] evaluate

[0183] (Method for measuring line resistance)

[0184] Using a measuring instrument (KEITHLEY, 2000 MULTIMETER), both ends of a linear metal film formed with two-terminal probes were brought into contact with each other to measure the line resistance value.

[0185]

[0186]

[0187] (Examination of Results of Examples and Comparative Examples)

[0188] (1) Embodiment

[0189] Examples 1 to 6 of the present application are copper pastes including copper hydride particles and a dispersion medium.

[0190] Since Examples 1 to 6 do not contain copper particles, Examples 1 to 4 and 6 can obtain metal films having very low resistance (metal films having excellent electrical conductivity) even when sintered in an air atmosphere.

[0191] Furthermore, since the copper hydride particles of Examples 1 to 6 were not coated with the long-chain organic compound, a conductive film having excellent conductivity was obtained by sintering at a low temperature and for a short time.

[0192] Example 1 uses water as a dispersion medium, whereas Example 5 uses BCA as a dispersion medium. As can be seen from the results in Table 2, Example 1 using only water as a dispersion medium obtains a further lower line resistance than Example 5, and when water is used as a dispersion medium, a metal film with further excellent conductivity can be obtained.

[0193] Example 4 uses BCA as a dispersant and acrylic resin as a binder. In contrast, Example 6 uses BCA as a dispersant but does not use acrylic resin as a binder. According to the evaluation results in Table 2, Example 4 using a binder achieves a lower line resistance than Example 6. That is, it is known that when BCA is used as a dispersant, a metal film with even better conductivity can be obtained if a binder is used in combination.

[0194] In Example 5, as a difference from the other examples, sintering was performed in a nitrogen atmosphere. Even if sintering was performed at a low temperature of 120°C and for a short time of 5 minutes, a very low line resistance was obtained. In addition, if sintering was performed at a temperature of 200°C for 5 minutes, a very low line resistance could be obtained, and very excellent conductivity could be achieved.

[0195] (2) Comparative Example

[0196] In Comparative Example 1, only 0.4 g of 1-micron spherical copper powder (Mitsui Kinzoku Co., Ltd., 1100YM) was added as a difference from Example 1. However, after sintering in air atmosphere, the line resistance became infinite, and the conductivity confirmed in other Examples was not observed.

[0197] Comparative Example 2 is an example in which the same copper paste as Comparative Example 1 was sintered in a nitrogen atmosphere. However, after low-temperature sintering at 120°C, the line resistance became infinite, and conductivity could not be confirmed. After sintering at 200°C in a nitrogen atmosphere, conductivity could be confirmed, but the line resistance was very large, so it could not be considered to be a conductive film with excellent conductivity.

[0198] Industrial Applicability

[0199] The copper paste of the present invention can be used to obtain a metal film with excellent conductivity. By using such a metal film as an electrode, a solar cell with excellent electrical properties can be obtained. Therefore, the copper paste of the present invention can be widely used in the field of solar cells.

Claims

1. A copper paste comprising copper hydride particles and a dispersion medium, but not containing copper particles. 2 . The copper paste according to claim 1 , which does not contain a conductive filler other than the copper hydride particles. 3 . The copper paste according to claim 1 , comprising only the copper hydride particles as a conductive phase.

4. The copper paste according to claim 1, wherein The dispersion medium is a liquid dispersion medium.

5. The copper paste according to claim 4, wherein The dispersion medium is a liquid dispersion medium having a hydroxyl group.

6. The copper paste according to claim 5, wherein The liquid dispersion medium having hydroxyl groups is water, an alcohol dispersion medium or an ether dispersion medium.

7. The copper paste according to any one of claims 4 to 6, wherein The liquid dispersion medium is only water.

8. The copper paste according to claim 1, wherein The surfaces of the copper hydride particles are coated with formic acid.

9. The copper paste according to claim 1, wherein The surfaces of the copper hydride particles are not coated with long-chain organic compounds.

10. The copper paste according to claim 1, wherein The content of the dispersion medium is 0.05 to 1 part by weight relative to 1 part by weight of the copper hydride particles. The copper paste according to claim 1 , further comprising a resin binder.

12. The copper paste according to claim 11, wherein The content of the resin binder is 0.0001 parts by weight or more and less than 0.05 parts by weight relative to 1 part by weight of the copper hydride particles.

13. A method for producing a copper paste, the method comprising: a step of dispersing copper hydride particles in a dispersion medium, This method does not add copper particles. 14 . The method for producing a copper paste according to claim 13 , wherein no conductive filler other than the copper hydride particles is added.

15. The method for producing a copper paste according to claim 13, wherein: The conductive phase of the copper paste is only the copper hydride particles.

16. The method for producing a copper paste according to claim 13, wherein: The dispersion medium is a liquid dispersion medium.

17. The method for producing a copper paste according to claim 16, wherein: The dispersion medium is a liquid dispersion medium having a hydroxyl group.

18. The method for producing a copper paste according to claim 17, wherein: The liquid dispersion medium having hydroxyl groups is water, an alcohol dispersion medium or an ether dispersion medium.

19. The method for producing a copper paste according to any one of claims 16 to 18, wherein: The liquid dispersion medium is only water.

20. The method for producing a copper paste according to claim 13, wherein: The surfaces of the copper hydride particles are coated with formic acid.

21. The method for producing a copper paste according to claim 13, wherein: The dispersion medium is used in an amount of 0.05 to 1 part by weight based on 1 part by weight of the copper hydride particles.

22. The method for producing a copper paste according to claim 13, wherein: In the step of dispersing the copper hydride particles in the dispersion medium, the copper hydride particles are dispersed in a mixture of the dispersion medium and a resin binder.

23. The method for producing a copper paste according to claim 22, wherein: The amount of the resin binder added is 0.0001 parts by weight or more and less than 0.05 parts by weight relative to 1 part by weight of the copper hydride particles.

24. A method for forming a metal film, the method comprising: A step of sintering the copper paste according to any one of claims 1 to 12 in an atmosphere containing oxygen.

25. The method for forming a metal film according to claim 24, wherein: The sintering temperature is 200° C. or less, and the sintering time is 1 to 10 minutes.

26. The method for forming a metal film according to claim 24, wherein: The atmosphere containing oxygen is an air atmosphere.

Citation Information

Patent Citations

  • Metal hydride fine particle, method for producing same, liquid dispersion containing metal hydride fine particle, and metallic material

    WO2004110925A1